2021
DOI: 10.3892/etm.2021.10032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Notch, IL‑1 and leptin expression in colorectal cancer

Abstract: An increasing number of studies have shown that angiogenesis has an important role in the progression of cancer. The growth of a new network of blood vessels is crucial for tumor growth and metastasis, which is promoted by several proangiogenic factors. Leptin, an essential adipokine that is secreted from fat tissue, is one of these pro-angiogenic factors. It has been shown that the inhibition of leptin-induced angiogenesis resulted in decreased levels of vascular endothelial growth factor (VEGF)/VEGFR2, hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Also, leptin increases VEGF/VEGF R2 expression via the up-regulation of Notch and IL1, forming the Notch, IL1 and leptin cross-talk outcome (NILCO) pathway. Moreover, leptin induces the expression of Notch1-4/Jagged-1/delta-like canonical Notch ligand (Dll) 4, which plays an important role in Notch signalling pathway 33 , 51 , 52 . Furthermore, some studies indicated, that IL1 activates Notch signalling through NfkB activity 53 and leptin up-regulates IL1 via an NfkB-dependent mechanism 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, leptin increases VEGF/VEGF R2 expression via the up-regulation of Notch and IL1, forming the Notch, IL1 and leptin cross-talk outcome (NILCO) pathway. Moreover, leptin induces the expression of Notch1-4/Jagged-1/delta-like canonical Notch ligand (Dll) 4, which plays an important role in Notch signalling pathway 33 , 51 , 52 . Furthermore, some studies indicated, that IL1 activates Notch signalling through NfkB activity 53 and leptin up-regulates IL1 via an NfkB-dependent mechanism 32 .…”
Section: Discussionmentioning
confidence: 99%
“…1D). In addition, to the well-known upregulation of genes involved in mucin processing and secretion such as MUC2, over representation analysis of the common upregulated genes revealed a prominent activation of in ammatory chemokines such as CXC motif chemokine ligand (CXCL) 8, CXCR1 and CXCR2 receptor and IL-1β in ammosome [27] (Fig. 2A).…”
Section: Low Expression Of Ly6g6d Characterizes Mucinous Colon Adenocarcinomamentioning
confidence: 96%
“…1D). In addition to the well-known MUC2 gene involved in mucin processing and secretion, analysis of the upregulated genes revealed pathways not previously known to be overexpressed in mucin cancer, including inflammatory chemokines such as CXC motif chemokine ligand (CXCL) 8, CXCR1 and CXCR2 receptor, and IL -1β-inflammosome [30] (Fig. 2A).…”
Section: Downregulation Of Ly6g6d Characterizes Mucinous Colon Adenoc...mentioning
confidence: 99%